Fetoprotective activity of breast cancer resistance protein (BCRP, ABCG2): expression and function throughout pregnancy - Hahnova-Cygalova, Lenka; Ceckova, Martina; Staud, Frantisek (Drug metabolism reviews, 2011)
The medical treatment of pregnant women, as well as their fetuses, has become a common clinical practice in developed countries. Therefore, detailed knowledge of maternofetal pharmacokinetics, including the role of drug-efflux transporters in the fetoplacental unit, is crucial to optimize drug choice and dosage schemes and to avoid or exploit possible drug-drug interactions on placental transporters in order to assure appropriate drug levels in the mother and/or fetus. Breast cancer resistance protein (BCRP, ABCG2) is the most recent member of ATP-binding cassette drug-efflux transporters that has been associated with resistance in cancer chemotherapy. Importantly, ABCG2 has also been localized in various normal tissues, affecting the pharmacokinetics of several xenobiotics as well as a number of physiological substances. Extensive expression of ABCG2 in tissue barriers, such as the blood-brain barrier, intestine, testis, or placenta, suggests that ABCG2 plays an important role in the protection of sensitive tissues against toxins. In the placenta, ABCG2 has been experimentally evidenced to actively pump its substrates in the fetal-to-maternal direction and to play an important role in transplacental pharmacokinetics, fetal protection, and detoxication. Further, ABCG2 expression in embryonic and fetal membranes over the course of pregnancy helps ensure proper function of the fetoplacental unit. In this review, we summarize the current knowledge regarding expression and function of ABCG2 in the fetoplacental unit during the development of the fetus and overview the aspects of transplacental pharmacokinetics, ABCG2 regulation, and clinical significance of the transporter for pharmacotherapy in pregnancy.
Keywords: xenobiotika; ATP-Binding Cassette Transporters; Animals; klinické zkoušky jako téma; ABC transportér z rodiny G, člen 2; plod; ATP Binding Cassette Transporter, Subfamily G, Member 2; Clinical Trials as Topic; Female; Embryo, Mammalian; Tissue Distribution; ženské pohlaví; Placenta; lidé; ABC transportéry; Fetus; těhotenství; Xenobiotics; polymorfismus genetický; tkáňová distribuce; nádorové proteiny; Neoplasm Proteins; zvířata; Pregnancy; placenta; Polymorphism, Genetic; embryo savčí; Humans